Economic costs of biological invasions in Ecuador: the importance of the Galapagos Islands - Liliana Ballesteros-Mejia; Elena Angulo; Christophe Diagne; Brian Cooke; Martin A. Nuñez; Franck Courchamp (NeoBiota, 2021)
Biological invasions, as a result of human intervention through trade and mobility, are the second biggest cause of biodiversity loss. The impacts of invasive alien species (IAS) on the environment are well known, however, economic impacts are poorly estimated, especially in mega-diverse countries where both economic and ecological consequences of these effects can be catastrophic. Ecuador, one of the smallest mega-diverse countries, lacks a comprehensive description of the economic costs of IAS within its territory. Here, using "InvaCost", a public database that compiles all recorded monetary costs associated with IAS from English and Non-English sources, we investigated the economic costs of biological invasions. We found that between 1983 and 2017, the reported costs associated with biological invasions ranged between US$86.17 million (when considering only the most robust data) and US$626 million (when including all cost data) belonging to 37 species and 27 genera. Furthermore, 99% of the recorded cost entries were from the Galapagos Islands. From only robust data, the costliest identified taxonomic group was feral goats (Capra hircus; US$20 million), followed by Aedes mosquitoes (US$2.14 million) while organisms like plant species from the genus Rubus, a parasitic fly (Philornis downsi), black rats (Rattus rattus) and terrestrial gastropods (Achatina fulica) represented less than US$2 million each. Costs of "mixed-taxa" (i.e. plants and animals) represented the highest (61% of total robust costs; US$52.44 million). The most impacted activity sector was the national park authorities, which spent about US$84 million. Results from robust data also revealed that management expenditures were the major type of costs recorded in the Galapagos Islands; however, costs reported for medical losses related to Aedes mosquitoes causing dengue fever in mainland Ecuador would have ranked first if more detailed information had allowed us to categorize them as robust data. Over 70% of the IAS reported for Ecuador did not have reported costs. These results suggest that costs reported here are a massive underestimate of the actual economic toll of invasions in the country.